PENGUATAN KOMPETENSI PENDIDIK MELALUI PEMANFAATAN GENERATIVE AI PADA MITRA SALASIKA INDONESIA - Liliana, Dewi Yanti; Marcheta, Noorlela; Delimayanti, Mera Kartika; Huzaifa, Malisa; Nalawati, Rizki Elisa (Jurnal AbdiMas Nusa Mandiri, 2026)
Generative Artificial Intelligence (GenAI) technology is increasingly used in the world of education. However, the low literacy of GenAI and the lack of educators' skills in utilizing it are challenges in its implementation. This community service activity aims to improve literacy and educators' skills in utilizing GenAI effectively and responsibly. The partner of the activity is the Mitra Salasika Indonesia Foundation, which houses teachers and lecturers with branches in six cities in Indonesia. The novelty of the program lies in the integration of GenAI literacy, prompting techniques, and GenAI ethics, which are delivered in workshops. The method of implementing the workshop was carried out in a hybrid format, with the delivery of GenAI material, accompanied by the practice of using the GenAI application to support learning, and workshop evaluation. Evaluation was carried out through pretest and posttest using the Likert scale (values 1 to 5), as well as feedback from participants. The results of the assessment showed an increase in pretest scores with an average score of 3.38, increasing to 4.57 in the posttest, or an increase of 35.16% after the workshop. This workshop is beneficial for educators at the Salasika Indonesia Foundation because it is relevant to work needs and useful to be applied directly in learning. This community service activity provides real benefits for educators and partner institutions, because through workshops that combine theory, practice, and discussion, educators' competence in dealing with the development of learning technology can be significantly increased.